SISTEM PAKAR DIAGNOSIS PENYAKIT TELINGA HIDUNG DAN TENGGOROK - Sifra M.B. Pattiasina; Chairisni Lubis; Agus Budi Dharmawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
Expert system is a system that is trying to adopt human knowledge into a computer, so that the computer can resolve the issue like done by experts. System design expert for disease diagnosis ear, nose and throat with the utilization of the basis knowledge on file in database. Expert systems to diagnose diseases of ear, nose and throat using Forward Chaning methods and Generate and Test Algorithms which aims to carry out a search about indications in order to diagnose type of disease. Forward Chaining using Certainty Factor to calculate the level of certainty of the disease diagnose.Generate and Test Algorithm to do a searching for indication in the form of question. The system will provide questions to be answered. Data that is recognizable will adjust the rules to matched then be calculated using Certainty Factor and gives weight of the resulting answers to diseases diagnose.